Carrying capacity of Mussoorie - Ramachandran, H.; Ramachandran, Nira (New Delhi Concept publishing, 2001)
It is a quantitative concept, involving parameters such as population (including both permanent and seasonal) and its future projection, land use, water supply, living accommodation for population, public health services, waste disposal, education, electricity, transport, communication and so on, the optimum requirements to be projected for a reasonable quality of living level.
Keywords: Substainable development